Effect of errorless and errorful learning on performance kinematic parameters in a throwing task: A pilot study - Behrouz Abdoli; Fariba Hasan Barani; Alireza Farsi (Vesnu Publications, 2014)
Abstract Introduction: to study the differences between effect of errorless and errorful learning on performance kinematic parameters. Material and Methods: 24 female students involved in three errorless, errorful and constant groups. The throwing instruction was not given to the groups. Errorful group practiced respectively at 2.5, 2.75, 3, 3.25, 3.5 meters, errorless group practiced in contrast with errorful group and constant group only from 3 meter began to practice. After three days of practice, acquisition, retention and transfer tests were done. Motion analysis machine was used to collecting the kinematic data in all periods. Results: in the retention test, the errorless group performance was significantly better than other two groups and in transfer test, the errorful group performance decreased. In performing of secondary cognitive task was not found significant differences between errorless and constant groups. In kinematic data analysis, the errorless group reached to the motor task skilled model but the errorful group was far from performance of motor task skilled model. Conclusion: The errorless learning is an efficient method in throwing skill learning of this study. Key words, errorless learning, errorful learning, performance kinematic parameters, skilled model, neuropsychological Rehabilitation.